Evaluasi Komunikasi Politik antara Elit Politik dengan Masyarakat Kecamatan Ilir Timur III Kota Palembang - Ibrahim Ibrahim; Adriansyah Adriansyah (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study discusses the evaluation of political communication between the political elite and the community in 9 Ilir Village, Ilir Timur III District, Palembang City. In this study, the approach used is a qualitative approach, with 6 informants. This research was conducted in 9 Ilir Village, Ilir Timur III District, Palembang City. Data collection techniques using observation techniques, interviews and documentation. The data analysis technique used interactive analysis with steps of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the evaluation of political communication between political elites and the community in 9 Ilir Village, Ilir Timur III District, Palembang City so far has gone well, this can be seen from the political communication process of the political elite, in simple terms, the communication process consists of several elements, namely: Communicate as a giver of information; Information, data, facts, or opinions as the message conveyed; and Communicators as recipients of information. In addition, communication will require media or means in the process of delivering information from the communicant to the communicator. After the delivery of information occurs, then there will be reciprocity of the communication process. Likewise, in political communication, in the process there is an exchange of political information from the communicant to the communicator.